Marine plastic: The solution is bigger than removal - García-Hermosa, M. Isabel; Woodall, Lucy C. (Frontiers in Sustainability, 2023)
Despite the increase in the documentation on, and interest in marine debris, there remains a gap between the analytic information available and the recommendations developed by policy and decision makers that could reduce this pollutant. Our paper summarizes some successful initiatives across policy, industry, infrastructure and education; and where they sit in the value chain of plastic products. We suggest that a multidisciplinary approach is required to most effectively address the marine plastic litter problem. This approach should emphasize (1) minimizing plastic production and consumption (where possible), and waste leakage; by (2) improving waste management (taking into consideration the informal sector) rather than focussing on clean-up activities. We then suggest some steps that once addressed would assist policy professionals, and a wide variety of entities and individuals with decision-making to reduce marine plastic litter. We suggest the creation of a user-friendly framework (tool) would facilitate transparency and democratization of the decision-making process across stakeholders and the wider community. This tool would be most useful if it comprised information on (i) defining appropriate metrics for quantifying plastic waste for the study/work case; (ii) providing a list of possible interventions with their key associated enabling and disabling factors, (iii) identifying the main influential factors specific to the situation/region; (iv) recognizing the risks associated with the selected interventions and the consequences of these interventions on the most influential factors; (v) objectively ranking solutions using the information gathered (metrics, targets, risks, factors) based on the regional, national, and/or international context. This tool then provides an opportunity for user groups to explore different suites of options for tackling marine plastic pollution and co-create a suite that is optimum for them.